Pengetahuan Sikap Dan Perilaku Masyarakat Terkait Mitigasi Bencana Tsunami Di Kelurahan Talise Kecamatan Mantikulore Kota Palu - Karmila; Rahmawati (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
This research focused on how well the people of Talise Village are prepared to deal with a tsunami. This research aimed to assess the general awareness of tsunami preparedness in Talise Village. Using a questionnaire based on field research findings, we could gauge how prepared the local community was to deal with the aftermath of a wave. Using the Slovin formula to determine the sample size, the researcher collected data through observation, interview, survey, and documentation techniques. The researcher then used a Likert scale and data from a modified questionnaire to analyze the collected information. The overall RW knowledge results showed that the community scored between 71% and 100% under the category